Probing the Scope of the Amidine–1,2,3‐triazine Cycloaddition as a Prospective Click Ligation Method - Siegl, Sebastian J.; Vrabel, Milan (European journal of organic chemistry, 2018)
Despite recent achievements in the development of chemical reactions enabling selective modification of complex biomolecules, the demand for fast and efficient methodologies that allow the attachment of various functional groups to these systems is the subject of intense research. Here, we report on the study of the amidine–1,2,3‐triazine cycloaddition reaction, which has the potential to address many of the challenges associated with the development of such chemistry. We describe an optimized protocol leading to the in situ formation of free amidine bases, which directly react in the cycloaddition reaction with 1,2,3‐triazines. Our kinetic studies reveal the structural features determining the reaction rates. Finally, we show that the amidine–1,2,3‐triazine cycloaddition is extraordinarily selective and orthogonal to other popular ligation reactions. The pros and cons of the methodology are presented. The amidine–1,2,3‐triazine cycloaddition was studied as a click ligation method. A new protocol for base‐promoted in situ formation of free amidine bases undergoing cycloaddition with 1,2,3‐triazines is reported. The reaction shows excellent orthogonality to strain‐promoted azide–alkyne cycloadditions or trans‐cyclooctene–1,2,4,5‐tetrazine cycloadditions. Limitations and advantages of the reaction are disclosed.